2017
DOI: 10.1002/biot.201600697
|View full text |Cite
|
Sign up to set email alerts
|

Production of taxadiene by engineering of mevalonate pathway in Escherichia coli and endophytic fungus Alternaria alternata TPF6

Abstract: Taxol (paclitaxel) is a diterpenoid compound with significant and extensive applications in the treatment of cancer. The production of Taxol and relevant intermediates by engineered microbes is an attractive alternative to the semichemical synthesis of Taxol. In this study, based on a previously developed platform, the authors first established taxadiene production in mutant E. coli T2 and T4 by engineering of the mevalonate (MVA) pathway. The authors then developed an Agrobacterium tumefaciens-mediated transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…2 ) 3 , 15 , 16 , both of which are required for coordination to the 3 Mg 2+ ions necessary for catalysis. To confirm the predicted coding sequence of AaTPS, genomic DNA of this gene was put under the control of the alcA promoter and transformed into A. alternata TPF6 via the Agrobacterium tumefaciens -mediated transformation method to generate mutant Alternaria alternata GB171 17 . Transcription data were gathered and the mRNA sequence of AaTPS was confirmed.…”
Section: Resultsmentioning
confidence: 99%
“…2 ) 3 , 15 , 16 , both of which are required for coordination to the 3 Mg 2+ ions necessary for catalysis. To confirm the predicted coding sequence of AaTPS, genomic DNA of this gene was put under the control of the alcA promoter and transformed into A. alternata TPF6 via the Agrobacterium tumefaciens -mediated transformation method to generate mutant Alternaria alternata GB171 17 . Transcription data were gathered and the mRNA sequence of AaTPS was confirmed.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the genera Pseudomonas and Sphingomonas in the seed microbiome are likely to be important reservoirs of rhizosphere or endosphere microbiome. Regarding the shared fungal core taxa, genus Alternaria can be a potential plant pathogen, but it also includes beneficial endophytes as biocontrol agents or other active compounds producing microbes [ 49 , 50 , 51 , 52 ]. Therefore, Alternaria can affect the germination of seeds and the assemblage of plant microbiome, and consequently, the growth and fitness of plants.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that the biosynthesis of sterols started with IPP and DMAPP, two C5 isoprene units synthesized by the MVA pathway ( Engels et al, 2008 ; Cha et al, 2012 ; Bian et al, 2017 ). Total genome sequencing and mRNA sequencing of NK17 were performed to identify the MVA pathway genes in NK17 via protein sequence BLASTP on NCBI.…”
Section: Resultsmentioning
confidence: 99%
“…In fungi, terpenoids are usually synthesized from two C 5 units, isopentenyl pyrophosphate (IPP) and dimethylallyl pyrophosphate (DMAPP) ( Li et al, 2015 ). These two units were condensed via the mevalonate (MVA) pathway and undergo a cyclization step to form terpenoid precursors by various terpene synthases, e.g., monoterpene synthase ( Lange, 2015 ), sesquiterpene synthase ( Wang et al, 2016 ), diterpene synthase, triterpene synthase ( Dhingra and Cramer, 2017 ), and even taxadiene synthase ( Bian et al, 2017 ). Due to bioactivities, many of them have been used in diverse fields, such as medicinal chemistry ( Austin et al, 1988 ), food additives ( Ravichandran et al, 2018 ), and biofuels ( Wu et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%